An Analysis of the Islamic Fiscal Policy of the State of Kuwait - Arum Teguh Fitriyani (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Kuwait is a Muslim-majority country and one of the largest oil-producing countries in the world. Fiscal policy in Kuwait can be based on several important factors that affect the country's economy, especially related to dependence on oil revenues, efforts to diversify the economy, and fiscal stability amid global oil price volatility. This research has a descriptive attitude, the method used in this research usesLibrary Research. The results of the study explain about fiscal policy in the State of Kuwait, the development of waqf in Kuwait has passed a very long history. Currently, zakat and waqf in Kuwait are managed with a good and advanced governance concept, through the existence of KAPF. Good governance of zakat has a positive impact on the increase in income from waqf as well as the development of capital goods that continue to grow. Kuwait has a good distribution system involving communities and families.